PENGARUH PENAMBAHAN METHYL TESTOSTERON DALAM PAKAN TERHADAP NISBAH KELAMIN IKAN GUPPY (Poeocilia reticulate Peters) - ., Suwarsito; Syarifuddin, Hamzah; Mulia, Dini Siswani (Universitas Muhammadiyah Purwokerto, 2007)
This research was conducted to knowÂ the effect of methyltestosteron dietary on sex ratio of guppy and determine the effective dosage of methyltestosteron. This research used experimental method with Completely Randomize Design condist of 4 treatments and replicates. The treatmens were P1 (0 mg/kg), P2 (10 mg/kg) P3 (20 mg/kg), and P4 (30 mg/kg), respectively. Observation of phenotype sex had done by identified of body style and morphologys variety. Percentage of sex ratio and survival rate of guppy were analyzed by ANOVA (Analysis of Variance) and LSD (Least Significant Difference Test). Results of the research showed thatÂ methyltestosteron dietary had effect on sex ratio of guppy (P<0,1), but had no effect on survival rate of guppy (P>0,05). The dosage of 10 mg/kg feed) result the highest percentage of male (61.69%).Â